2022
DOI: 10.3390/jof8080816
|View full text |Cite
|
Sign up to set email alerts
|

D-Lactic Acid Production from Sugarcane Bagasse by Genetically Engineered Saccharomyces cerevisiae

Abstract: Lactic acid (LA) is a promising bio-based chemical that has broad applications in food, nutraceutical, and bioplastic industries. However, production of the D-form of LA (D-LA) from fermentative organisms is lacking. In this study, Saccharomyces cerevisiae harboring the D-lactate dehydrogenase (DLDH) gene from Leuconostoc mesenteroides was constructed (CEN.PK2_DLDH). To increase D-LA production, the CRISPR/Cas12a system was used for the deletion of gpd1, gpd2, and adh1 to minimize glycerol and ethanol producti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 40 publications
1
5
0
Order By: Relevance
“…In fact, studies such as that of Van maris et al argue that to increase LA production, it is necessary to suppress pyruvate decarboxylase activity (van Maris et al, 2004). A third one, GPD1, which encodes glycerol-3-phosphate dehydrogenase implicated in the balance of NADH oxidation and intracellular accumulation of glycerol (Albertyn et al, 1994); as in the case of the PYC genes, we also found evidence in the literature for the GPD1 gene indicating that knockout of the latter is functional for LA optimization, because the knockout of the GPD1 gene leads to minimize the production of ethanol and glycerol (Sornlek et al, 2022).…”
Section: δPsd1(xiv)supporting
confidence: 62%
“…In fact, studies such as that of Van maris et al argue that to increase LA production, it is necessary to suppress pyruvate decarboxylase activity (van Maris et al, 2004). A third one, GPD1, which encodes glycerol-3-phosphate dehydrogenase implicated in the balance of NADH oxidation and intracellular accumulation of glycerol (Albertyn et al, 1994); as in the case of the PYC genes, we also found evidence in the literature for the GPD1 gene indicating that knockout of the latter is functional for LA optimization, because the knockout of the GPD1 gene leads to minimize the production of ethanol and glycerol (Sornlek et al, 2022).…”
Section: δPsd1(xiv)supporting
confidence: 62%
“…The engineered strain, when subjected to SSF using alkaline-pretreated sugarcane bagasse, achieved an impressive d -LA yield of 0.33 g per g-glucan. 30 This outcome underscores its potential for the production of industrially valuable products. The genetic-engineering approaches have been exploited in a big way for the improvement of LA yield and optical purity by various microbial producers.…”
Section: Resultsmentioning
confidence: 91%
“…28 Furthermore, author keywords like “metabolic engineering”, “ Saccharomyces cerevisiae ”, and “ Escherichia coli ” hold the 10th, 11th, and 24th rankings, respectively. Of notable significance, extensive research has been undertaken on the production of LA from LCB through metabolically engineered S. cerevisiae 29,30 and E. coli . 31–33 Additionally, LA often emerges as a byproduct in systems where S. cerevisiae produces ethanol from LCB.…”
Section: Resultsmentioning
confidence: 99%
“…The quantification of D-lactic acid and other metabolites was performed as previously described, with some modifications [2,30]. The engineered strains were prepared by preculturing 5 mL aliquots in a yeast minimal medium (MGYH; 0.1 M phosphate buffer pH 6.0, yeast nitrogen base without amino acids (13.6 g/L), glycerol (20 g/L), D-biotin (0.4 mg/L), thiamine-hydrochloride (133.3 mg/L), and L-histidine (20 mg/L)).…”
Section: Quantifying Production Of D-lactic Acid and Other Metabolitesmentioning
confidence: 99%
“…High-performance liquid chromatography (HPLC) was used to measure the amount of D-lactic acid and other fermentation metabolites, including ethanol, glycerol, pyruvate, acetate and glucose, as previously described [2,30]. One mL of yeast culture was passed through a 0.2-micron nylon syringe filter (Filtrex, Bangkok, Thailand).…”
Section: Quantifying Production Of D-lactic Acid and Other Metabolitesmentioning
confidence: 99%